THREE STATE LOGIC PROBE - Adi Faizal; Drs. Lingga Hermanto, MMSI (Jurnal Sistem Komputer, 2005)
Created a logic level detection circuit of a digital circuit. This circuit has the ability to3 (three) logic level digital signal is typically defined as follows: Level of highvoltage (High), low voltage level (Low) and the threshold voltage level (Theresehold).The ability of this series allows a digital circuit analysis to help level the better. Inthis series of tests in particular applied to the gates of the base.